2014
DOI: 10.1177/0954405414555591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external magnetic field on weld pool flow conditions in high-speed gas metal arc welding

Abstract: In high-speed gas metal arc welding process, weld defects like humping bead and undercutting appear and the weld bead quality worsens when welding speed exceeds a critical value. The previous investigations have proved that the backward flowing molten jet with high momentum in the weld pool is responsible for the formation of humping bead in high-speed gas metal arc welding. In this study, an external electromagnetic field generator is developed to change and control the flow condition in the weld pool and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Wu et al. [ 32 ] stated that “EMF” regulates the “speed” of the “retrograde-flow” of the “weld-pool” and holds the “bead-crown” at increased “weld speed”. Nomura et al.…”
Section: Trends and Advancements In Emf-assisted Welding-processmentioning
confidence: 99%
“…Wu et al. [ 32 ] stated that “EMF” regulates the “speed” of the “retrograde-flow” of the “weld-pool” and holds the “bead-crown” at increased “weld speed”. Nomura et al.…”
Section: Trends and Advancements In Emf-assisted Welding-processmentioning
confidence: 99%
“…Shoichi et al [26] used an upward electromagnetic force to lift the molten metal up in flat hot wire TIG welding with excessive heat input, and the hump defect was significantly suppressed. Wu et al [27,28] applied an external transverse magnetic field to the weld pool to control the behavior of the liquid metal, and successfully prevented the weld bulge. Gatzen et al [29] used a coaxial magnetic field to control the flow of molten metal through electromagnetic stirring.…”
Section: Introductionmentioning
confidence: 99%
“…The application of magnetic field in laser and arc welding with obviously effect in improving the quality of the welding bead due to its Hartman and thermoelectrical effect [27][28]. Wu, C et al [29] found that the external magnetic field can remarkably adjust the weld pool fluid flow field and decrease the momentum of the backward flowing molten jet, and the quality of the weld bead is remarkably improved. Avilov et al [30] verified that the surface tension cannot stop the gravity drop without the support from external magnetic field.…”
Section: Introductionmentioning
confidence: 99%